Additions to the Knowledge of the Fungal Order Eurotiales in Korea: Eight Undescribed Species - Thuong T. T. Nguyen; Ki Hyun Kang; Dong Hee Kim; Su Jin Kim; Hye Yeon Mun; Wonsu Cheon; Hyang Burm Lee (Mycobiology, 2023)
Eurotiales is a relatively large order of Ascomycetes, well-known for their ability to produce secondary metabolites with potential beneficial applications. To understand their diversity and distribution, different environmental sources including soil, freshwater, insect, and indoor air were investigated. Eight strains of Eurotiales were isolated and identified based on their morphological characters and a multi-gene phylogenetic analysis of the ITS, BenA, CaM, and RPB2 regions. We identified eight taxa that were previously not reported from Korea: Aspergillus baeticus, A. griseoaurantiacus, A. spinulosporus, Penicillium anthracinoglaciei, P. labradorum, P. nalgiovense, Talaromyces atroroseus, and T. georgiensis. Detailed descriptions, illustrations, and phylogenetic tree for the eight new records species are presented, and information regarding the records is also discussed.